Non-Native EFL Teachers’ Beliefs and Classroom Practices in English Teaching for Young Learners: A Narrative Inquiry - Elsi Yunita; Rahmah Fithriani; Ernita Daulay (Journal of General Education and Humanities, 2026)
Teaching English to young learners poses challenges for non-native EFL teachers, particularly in balancing curriculum demands with fostering an engaging, supportive classroom environment. This study aims to explore the beliefs and classroom practices of non-native EFL teachers in teaching English to young learners. A narrative inquiry approach was employed to investigate how teachers’ experiences and beliefs influence their instructional strategies. The study was conducted at an international primary school in Medan, Indonesia, involving three experienced non-native English teachers. Data were collected through narrative interviews, classroom observations, and document analysis of lesson plans and teaching materials. Findings indicate that teachers’ beliefs are shaped by their personal teaching experiences, caregiving roles, and ongoing interactions with young learners. They prioritize creating enjoyable, emotionally supportive, and student-centered learning environments, which is reflected in practices such as games, songs, storytelling, movement-based activities, and positive reinforcement. Despite challenges posed by curriculum requirements and full-day school schedules, teachers adapt their strategies while maintaining their core beliefs. The study highlights that teachers’ beliefs are dynamic and enacted through classroom experiences, providing insights into the meaningful connection between beliefs and practices in EFL teaching for young learners.